Integrated plasma metabolomic and proteomic analysis uncover the effects and mechanisms of isotretinoin in severe acne - Xia, Manqi; Zhang, Jing; Hu, Yang; Chen, Ziyan; Ke, Yanan; Zhang, Shujuan; Yang, Zeen; Tian, Xin; Liang, Jingyao; Liu, Yumei (Frontiers in Pharmacology, 2025)
BackgroundAcne vulgaris is a prevalent chronic inflammatory disorderof the skin and oral isotretinoin is one of the most effective treatments forsevere acne with incompletely understood mechanisms. The aim of thisstudy was to investigate the pathogenesis of acne and the therapeuticmechanisms underlying isotretinoin treatment from integrated human plasma metabolomics and proteomics.MethodsLiquid chromatography-tandem mass spectrometry (LC-MS/MS) full-spectrum metabolomics and four-dimensional data-independent acquisition (4D-DIA) quantitative proteomics were employed to analyze plasma samples from patients with group AG (severe acne group), group AG1 (severe acne group1, before isotretinoin treatment), group TG (isotretinoin treatment group) and group CG (control group). Bioinformatics statistical analysis were employed to analyze the metabolomic and proteomic data.Results489 differentially expressed metabolites (DEMs) were detected in the plasma from patients with severe acne compared to controls. Isotretinoin treatment normalized the dysregulation of 94 metabolites, including inositol 1,3,4-trisphosphate (Ins(1,3,4)P3), 11-cis-retinol, thyroxine (T4), androstenediol, estrone 3-sulfate, bovinicacid, n-oleoylethanolamine, LPS(20:1), Cer(d16:1/23:0) and TG(17:1 18:2 18:3). Additionally, 36 differentially expressed proteins (DEPs) were identified in patients before and after isotretinoin treatment. Notably, downregulation of acyl-CoA synthetase long-chain family member 4 (ACSL4) suggests a potential therapeutic mechanism for isotretinoin, while upregulation of monoacylglycerol O-acyltransferase 2 (MOGAT2) may mediate the elevation of blood lipids and the correction of some abnormal lipids. Isotretinoin modulates multiple pathways, including inositol phosphatemetabolism, glycerolipid metabolism, thyroid hormone synthesis and insulin resistance.ConclusionImportant DEMs, DEPs and metabolic pathways were identified in this study, which will help clarify the pathogenesis of acneand the potential mechanisms of isotretinoin in the treatment of acne, andidentify novel targets for severe acne treatment and side effect reduction.